بعض العناصر المؤثرة في تحسين فاعلية التدقيق الخارجي في مكاتب التدقيق الأردنية : دراسة ميدانية من وجهة نظر مدققي الحسابات الخارجيين - الذيبة، زياد عبدالحليم; أبو قبع، حمزة يوسف Abu Qaba, Hamzah Yousef (جامعة لونيسي علي البليدة 2 - مخبر التنمية الاقتصادية والبشرية, 2017)
This study aimed at identifying the impact of needed factors such as the criteria for selecting auditors, auditor’s independence, auditor’s fees, auditor industry specialization in improving the efficiency of external auditing in Jordanian auditing firms from the perspective of external auditors. The researchers adopted an analytical descriptive approach . The study came up with a number of findings, chief among which was the existence of a positive effect of the independent variables of the study (combined and separated) in enhancing the efficiency of external auditing in Jordanian external auditing firms. The study concluded with a number of recommendations chief among which was that auditors should do their job according to auditor industry specialization. Also legal protection should be provided for external auditors so that they could maintain their independence.
هدفت هذه الدراسة إلى تحديد أثر العناصر والمتمثلة في أسس اختيار المدقق، واستقلالية المدقق، وأتعاب المدقق، والتخصص المهني للمدقق في تحسين فاعلية التدقيق الخارجي في مكاتب التدقيق الأردنية، وذلك من وجهة نظر المدققين الخارجيين الأردنيين، وقد قام الباحثان باتباع المنهج الوصفي التحليلي في الدراسة ومن أهم النتائج التي توصلت إليها الدراسة، وجود تأثير إيجابي لمتغيرات الدراسة المستقلة (مجتمعة ومتفرفة) في تحسين فاعلية التدقيق الخارجي في مكاتب التدقيق الأردنية، وقدمت الدراسة العديد من التوصيات، أهمها: أنه ينبغي على المدققين القيام بممارسة المهنة وفقاً للتخصص المهني، وضرورة توفير الحماية القانونية اللازمة للمدقق الخارجي حتى يحافظ على استقلاليته.
Keywords: مدققي الحسابات; التدقيق الخارجي; الأردن; مراجعة الحسابات